Knowledge, Attitude and Practice of Dental Practitioners Towards Management of Endodontically Treated Teeth - Joshi, Barsha; Gautam, Suman; Joshi, Rojin; Khapung, Anju (Nepal Medical College Journal, 2025)
The restoration of endodontically treated teeth (ETT) is a vital aspect of dental care, influencing long-term tooth survival and overall oral health. This descriptive, cross-sectional survey assessed the knowledge, attitudes, and practices of 201 dental practitioners in Kathmandu Valley regarding post-endodontic restoration. Results showed that most participants demonstrated strong theoretical knowledge, with 63.2% favoring post and core restorations and 87.5% recognizing the importance of a ferrule. While positive attitudes was showed by a large percentage 87.4% which agreed on the significance of restoring ETT, while practical implementation was inconsistent. Notably, only 19.8% consistently used a rubber dam despite 90.5% acknowledging its necessity. Most participants, 97.5% adapted techniques based on clinical conditions, and 96.5% engaged in continuing education. The study highlights a knowledge-practice gap, especially in infection control and post utilization of technique. These findings underscore the need for targeted clinical training and standardized protocols to ensure evidence-based, consistent restoration practices for improved patient outcomes.